General Social Function for Elderly in Geriatric Homes in Jordan - Nazar A. Sherin, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To assess general social factors for elderly in geriatric homes in Jordan.Methodology: The study was conducted for clients residing in elderly homes. A purposive sample of (155)residents were selected. Social resource scale by (Duck University Center) called (OARA) older adult resourcesand services was used as tool for data collection. The questions extract data about family structure, patterns offriends and visiting, availability of a confident, satisfaction with the degree of social interaction and availabilityof a helper in the event of illness or disability and the program of trips in the houses.Results: The findings revealed that the life expectancy for women is greater than for men. In respect to maritalstatus, the majority of the residents were widows who represented (38.I). Only ( 15.5%) of them were visited bytheir family more than (5) tines in the year. The study shows that (61.3%) of them have trust to the home's staffand (25.1%) to their friends in the home. In regard to loneliness, (66.5%) of them feels loneliness and they needoutside assistance, In regard to clients' help, (42%) of them could not know or answer this question. While,(51.6%) of them need help from inside on bathing, eating or taking medication. In relation to clients trips outsidehome, (54.8%) of them have the chance to go outside the home for trip; mainly for visiting family, friends or forreligious purposes.Recommendation: The study recommended that the leaders of the homes must focus on increasing the facilitiesof social relation through more communication, increase visiting times between the elderly and their familiesthrough the social worker of the house, get out of the house and meet other people, invite people home, an.angeregular tines for getting together with fiiends and family members, and find activities that involve doing things.